Potensi Sisik Ikan Nila (Oreochromis niloticus) dan Bawang Dayak (Eleutherine palmifolia L. Merr) sebagai Masker Collagen - Firlianty Firlianty; Elita Elita; Anang Najamuddin; Rario Rario; Panca Ajura Purba (Agrikan: Jurnal Agribisnis Perikanan, 2020)
This study aims to know the potential of collagen mask of nile tilapia scale and Dayakness onion. It was an experimental study with 3 treatments of different ethanol concentrations (50%, 70%, 90%). Data are presented. Data collection covered phytochemical tests, water content, ash, and pH. Results showed that the collagen mask of nile tilapia scale and Dayakness onion positively contained alkaloid, saponin, tannin, and flavonoid. These compounds reflect that collagen of Dayakness onion and nile tilapia scale is potential to use as face mask that could overcome face problem, such as acne. The collagen mask has pH of 6, consistent with that of SNI for facial beauty product. The nile tilapia scale and Dayakness onion have good potential for mask. The ethanol used for solvent yielding the highest collagen was recorded in 90% ethanol.